A new species of Stenodynerus de Saussure, 1863 (Hymenoptera: Vespidae: Eumeninae) from Lombok, with a key to the species from the Malay Archipelago - Selis, Marco (Zootaxa, 2019)
The genus Stenodynerus de Saussure, 1863 is recorded from Lombok Island for the first time with a new species, Stenodynerus lombokensis Selis, sp. nov. A checklist and a key to the species of Stenodynerus from the Malay Archipelago are provided.